79.1k views
0 votes
Simplify the following expression into simplest form with all positive exponents

Simplify the following expression into simplest form with all positive exponents-example-1

2 Answers

6 votes

Answer:

I'm am pretty sure that the answer is 320. Hope this helps!

User Just
by
6.0k points
6 votes

Hey there!


\mathsf{(7 * 10^8) - (4 *10^6)}


\mathsf{= 7*10^8 - 4*10^6}


\mathsf{10^8}


\mathsf{= 10 * 10 * 10 * 10 * 10 * 10 * 10* 10}


\mathsf{= 100 * 100 * 100* 100}


\mathsf{= 10,000*10,000}


\boxed{\mathsf{\bf = 100,000,000}}


\mathsf{7*100,000,000 - 4 *10^6}


\mathsf{10^6}


\mathsf{= 10 * 10 * 10 * 10 * 10*10}


\mathsf{= 100* 100*100}


\mathsf{= 10,000*100}


\boxed{\mathsf{= \bf 1,000,000}}


\mathsf{7 * 100,000,000 - 4 * 1,000,000}


\mathsf{7*100,000,000 = \boxed{\bf 700,000,000}}


\mathsf{700,000,000 - 4 *1,000,000}


\mathsf{4* 1,000,000 = \boxed{\bf 4,000,000}}


\mathsf{700,000,000 - 4,000,000}


\boxed{\mathsf{= \bf 696,000,000}}


\boxed{\boxed{\large\textsf{Answer: \huge \bf 696,000,000}}}\huge\checkmark


\large\textsf{Good luck on your assignment and enjoy your day!}

~
\frak{Amphitrite1040:)}

User Tillerino
by
6.2k points